Pilot-scale Study on Removal of Pollutants in Tannery Wastewater and Sludge Reduction by Biological Synergist Effect. Issue 3 (July 2020) - Zou, Xiaofeng; Ma, Fang; Yu, Jun; Su, Qiang; Gai, Lihong; Zhao, Wei; Ma, Kun; Wang, Jianguo; Tan, Xin; Sun, Fengmei; Xiao, Shuxin
Abstract: The characteristics of tannery wastewater are complex composition, high suspended substance (SS) and heavy sludge load. Adding the functional bacteria agent into the Aerobic system and Sludge digestion tank can improve the biological system activity and reduce sludge discharge. The pilot-scale study results show that: The removal of CODcr and NH3- N was improved after biological synergy. The average removal rate of CODcr was 90.1% and the average removal rate of NH3-N was 97.4%, both of which were higher than the control group. The excess sludge reduction of the system could reach 75.16%, and the effect of sludge reduction was obvious in the experimental group. After biological synergy, the number of bacteria in aerobic pool increased significantly, and the microbial flora migrated in a better direction.